A Morphological Study On English Compound Words Found In Handbook Of Psycholinguistics Subject At 7th Semester At Muhammadiyah University Of Surakarta - Wibowo, Andrevian Ari, Drs. Sigit Haryanto, M.Hum, Siti Fatimah, S.Pd, M.Hum (2014)
This study is focused on compound words that are found in Handbook of Psycholinguistics subject at 7th semester. This study is aimed to describe what the forms of compound word are and what the meanings of compound word are in Handbook of Psycholinguistics subject at 7th semester by using O'Grady's theory and Palmer's theory. This is a descriptive qualitative research. The object of this study is compound words. The technique of collecting data is documentation method. There are several procedures of collecting data such as reading the handbook, selecting compound words, and retyping. The data is analyzed using tree diagram (O'Grady's theory) and identifying meaning using Palmer's theory. The results of this study are 226 of compound words. Based on the forms of compound word, there are 158 (69,9%) 0f noun compound, 1 (0,4%) of verb compound and 67 (29,7%) of adjective compound. The total is 226 (100%) of compound words. Based on the meanings of compound, there are 184 (81,4%) of transparent meaning and 42 (18,6%) of opaque meaning. The total is 226 (100%) of compound words.